Hydraulic Flow through Engineering Bentonite-Based Containment Barriers - Loh, Eric Wooi Kee; Chitral Wijeyesekera, Devapriya (Science Publications, 2015)
This paper presents the use of software modelling as a tool to study the impact of hydraulic “resistivity” on the contaminant transport through bentonite-based containment barriers. A sensitivity analysis on the predicted data was carried out by varying the boundary conditions as well as the hydraulic resistance to flow through varying contaminant transport parameters. Accordingly, both advective and diffusive flow processes are considered as that which resists the flow. In particular, the effect on the contaminant migration due to desiccation cracking is explored. Laboratory evidence is provided and discussed to show how the initial microstructure of the clay influences the development of subsequent macro structural features such as shrinkage crack patterns. The effect of these cracks and the intensity of cracking on the contaminant migration are modelled and pragmatically discussed. Additionally, the effect on the hydraulic conductivity of bentonite-based barriers, when permeated with non-standard liquids is discussed and a typical analytical output is presented.